A Tale of Excessive Hospital Autonomy? An Evaluation of the Hospital Reform in Senegal - Lemière, Christophe (World Bank, Washington, DC, 2012)
This report evaluates the hospital reform that took place in Senegal in 1998. The reform was successful in granting hospitals considerable autonomy in all management areas, yet resulted in many hospitals closing to bankruptcy. After the reforms the population continued to regard hospital care as unaffordable and of inadequate quality. The very mixed results of the hospital reform are due to a lack of efficiency and built-in accountability. The report concludes that it might have been possible to avoid the current situation if in addition to empowering hospitals, an accountability mechanism had been implemented. The priorities will be to restore some government control over hospitals, restore the efficiency of hospitals, and create some progress on equity of access to hospital care.